Virtual planning and volumetric evaluation of wound healing following regenerative surgical treatment of intrabony periodontal defects. (June 2022) - Palkovics, Daniel; Solyom, Eleonora; Pinter, Csaba; Windisch, Peter
Abstract : Purpose: Our aim was to present a virtual surgical planning process in the regenerative treatment of intrabony periodontal defects and to evaluate volumetric and 3D morphological changes by the superimposition of pre- and post-operative cone-beam computed tomography (CBCT) datasets. Methods: Eight intrabony periodontal defects were enrolled in the present investigation. CBCT and intraoral scans (IOS) were taken prior to and 6 months after periodontal regenerative surgery. Utilizing a semi-automatic segmentation method 3D models were generated from CBCT scans using an open-source radiographic image processing software (3D Slicer). Hybrid models were acquired with the superimposition and subsequent free-form surface modeling of the segmented CBCT model and the IOS. Hybrid models visualizing all relevant anatomical structures separately (alveolar bone, teeth, soft tissues) were used to plan each step of the procedure virtually prior to surgery. Superimposition of the pre- and post-operative CBCT scans was performed to validate volumetric and 3D morphological alterations. Results: Based on the hybrid models, periodontal defect morphology was visualized in 3D. Following healing, hard tissue fill averaged at 43.04 mm 3 ± 24.47 mm 3 . Hard tissue resorption could be detected in three cases. Conclusion: Hybrid models acquired with the technique allowed a better understanding of the 3D defect morphology and therefore more precise surgical planning could be performed. With the spatial registration of pre- and post-operative CBCT scans volumetric and 3D morphological alterations could be visualized that provided a better understanding of the healing dynamics.